Effect of freezing on the viscoelastic behaviour of whey protein concentrate suspensions - Meza, Barbara Erica del Valle (2010)
The effect of freezing on viscoelastic behaviour of whey protein concentrate (WPC) suspensions was studied. Suspensions with total protein content of 5% and 9% w/v were prepared from a commercial WPC (unheated suspensions). A group of unheated suspensions was treated at two temperatures (72.5 and 77.5 C) during selected times to obtain 60% of soluble protein aggregates (heat-treated suspensions). Unheated suspensions and heat-treated suspensions were frozen at -25 C (frozen unheated and frozen heat-treated suspensions). Frequency sweeps (0.01-10 Hz) were performed in the region of linear viscoelasticity at 10, 20, 30, 40, and 50 C. Mechanical spectra of all studied suspensions at 20ºC were similar to viscoelastic fluids and complex viscosity increased with the frequency (w). Elastic (G´) and viscous (G") moduli were modelled using power law equations (G´=aw^x, G"=bw^y), using fitted parameters "a", "x", "b", and "y" for statistical analysis. Exponent "y" was the most influenced by freezing, indicating the existence of a higher degree of arrangement in frozen unheated suspensions and a lower degree of arrangement in frozen heat-treated suspensions. Only characteristic relaxation times (inverse of the crossover frequency) of suspensions with 5% w/v of total protein content were significantly influenced by freezing. Time-temperature superposition was satisfactory applied in unheated whey protein concentrate suspensions only in the range of high temperatures (30-50 C). However, this principle failed over the complete temperature range in most of the frozen suspensions. It is possible that freezing produced an increase in the susceptibility to morphological changes with temperature during the rheological measurements.